Rural Children’s Perceptions of Happiness: What is Happiness? How Do They Make You Happy? How Can They Be Happy? - Başaran, Mehmet; Öğretir Özçelik, Ayşe Dilek (My University, 2020)
This study aims to investigate the perception of happiness of children in the middle childhood stage and adolescents. In this context, it was sought to answer the questions of how children define happiness, how they make people around them happy, and what other people around them do to make them happy. Also, it was investigated whether there is a difference between children of middle childhood stage and adolescents regarding those questions. The research employed a qualitative phenomenological method, and the sample of the study was selected from a rural area of Ağrı province. The study group consisted of 95 participants 48 of whom are at middle chilhood and 47 pre-adolescents. Within the scope of the research, data were obtained through semi-structured interviews that were formed through expert opinions. Content and descriptive analyses were used in the analysis of the data. As a result of the research, it was found that there was a similarity between the methods of children’s making and being happy; however, there were some differences in terms of development levels and gender. Besides that, considering the obtained results, there was a consistency with the existing litreature aboutthe perceptions of happiness. The results were discussed in terms of the literature on happiness, and child development and education.

Bu araştırmanın amacı orta çocukluk dönemindeki çocukların ve ön ergenlerin mutlulukla ilgili algılarını incelemektir. Bu kapsamda çocukların mutluluğu nasıl tanımladıkları, çevresindeki insanları nasıl mutlu ettikleri ve çevresindeki insanlar ne yaptıklarında mutlu olduklarına dair sorulara cevap aranmış veortaya çıkan mutluluk algısında çocukların cinsiyeti ve yaşına göre bir farklılık olup olmadığı araştırılmıştır. Araştırma nitel araştırma yaklaşımında fenomonolojik araştırma olarak tasarlanmıştır. Araştırmanın çalışma grubu Ağrı ilinin kırsal bölgesinden seçilmiş 48’i orta çocukluk döneminde olan çocuk (yaş ort. 9), 47’si ise ön ergen (yaş ort.13)katılımcıdan oluşmaktadır. Araştırmanın verileri, uzman görüşleri sonucu oluşturulan yarı yapılandırılmış görüşmelerle elde edilmiştir. Verilerin analizinde içerik analizi kullanılmıştır. Araştırma sonucunda çocukların mutlu etme yolları ile mutlu olma yolları arasında bir benzerlik olduğu, yaş ve cinsiyet bakımından bazı farklılıkların ortaya çıktığı ve mutluluğa ilişkin algıların var olan literatürle uyumlu olduğu bulunmuştur. Elde edilen sonuçlar mutluluk ve çocuk gelişimi alanyazını açısından tartışılarak öğrenmen, ebeveyn ve araştırmacılara önerilerde bulunulmuştur.
Kırsalda Yaşayan Çocukların Mutluluğa İlişkin Algıları: Mutluluk nedir? Nasıl mutlu ederler? Nasıl mutlu olurlar?